Neuroregenerative Mechanisms of Allopregnanolone in Alzheimer’s Disease - Irwin, Ronald W.; Wang, Jun M.; Chen, Shuhua; Brinton, Roberta D. (Frontiers in Endocrinology, 2012)
The proliferative pool and regenerative potential of neural stem cells diminishes with age, a phenomenon that may be exacerbated in prodromal and mild Alzheimer’s disease (AD) brains. In parallel, the neuroactive progesterone metabolite, allopregnanolone (APα), along with a host of other factors, is decreased in the AD brain. Results of preclinical analyses demonstrate that APα is a potent inducer of neural progenitor proliferation of both rodent and human derived neural progenitor cells in vitro. In vivo, APα significantly increased neurogenesis within the subgranular zone of the dentate gyrus and subventricular zone of the 3xTgAD mouse model. Functionally, APα reversed the learning and memory deficits of 3xTgAD mice prior to and following the onset of AD pathology and was comparably efficacious in aged normal mice. In addition to inducing regenerative responses in mouse models of AD, APα significantly reduced beta-amyloid burden, ABAD load, and microglial activation. In parallel, APα increased markers of white matter generation and cholesterol homeostasis. Analyses to determine the optimal treatment regimen in the 3xTgAD mouse brain indicated that a treatment regimen of APα once per week was optimal for both inducing neurogenesis and reducing AD pathology. Pharmacokinetic analyses indicated that APα is rapidly increased in both plasma and brain following a single dose. APα is most efficacious when administered once per week which will contribute to its margin of safety. Further, analyses in both animals and humans have provided parameters for safe APα dosage exposure in humans. From a translational perspective, APα is a small molecular weight, blood brain barrier penetrant molecule with substantial preclinical efficacy data as a potential Alzheimer’s therapeutic with existing safety data in animals and humans. To our knowledge, APα is the only small molecule that both promotes neural progenitor regeneration in brain and simultaneously reduces AD pathology burden.